DAMPAK KERJASAMA MILITER AMERIKA SERIKAT-TAIWAN TERHADAP HUBUNGAN AMERIKA SERIKAT-CINA - Fajrian Eka Budi Darmawan; Ahmad Jamaan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The objective of this research has to analyze the impact of the several issues on realism, theresearch is to explain an impact from United States of America and Taiwan arms sale to the relationsbetween United States and China. United States has a military relations with Taiwan to manage andsupply their arms and weapons need and to identifying the interest of United States to becomeTaiwan biggest weapon supplier.According to realism, approach realism was a theory that explain the main interest of theperspective is to reach the struggle of power with Nation-state level analysis to describe that thestates is the main actor to security dilemma is concept from the realism theory that a nation thatincreasing a military budget and modernization will set another nation response and react toincreasing the military that will make the security policy has a reflection to compare their progress.China and United States was a closest and biggest nation-relation with a mutual relation on theeconomic, culture, and politic sector. In many chance, China and United States are not lack ofconflicts.The conclusion are China response to United States and Taiwan military arms salecooperative, which are China had to warning United States to stop their sales activity to Taiwan. Anincreasing at Taiwan military budget to bought the United States arms sale, been following by Chinato increasing the quantities of the weapons and the military budget to set the arms sale betweenChina and United States.Keywords: arms, impact, military, relations, realism, security dilemma